Enhancing Honey Production and Packaging in Jujun Village: A Strategic Approach to Kickstart Marketing Initiatives - Irawan, Bambang; Fazriyas, Fazriyas; Tamin, Rike Puspitasari; Anggraini, Riana; Ulfa, Maria (LPPM Universitas Jambi, 2023)
Honey is a valuable non-timber forest product widely consumed by communities, with those living near forests sourcing it both from the wild and cultivation. Jujun Village, supported by the Faculty of Agriculture at Jambi University, received assistance in honeybee farming through the Wira Desa program from the Department of Forestry in 2021. As a new venture, continued support was needed to strengthen its potential as an alternative economic source. This study aims to address the challenges of honey farming in Jujun through three main activities: (1) evaluating and strengthening beehive positioning based on natural forage availability to ensure consistent production; (2) improving group members’ skills in honey production and harvesting; and (3) enhancing packaging to facilitate market access. The program, conducted from March to August 2022, followed three phases: socialization, demonstration, and mentoring. Results showed significant improvements in participants' understanding of honey production, harvesting safety, product quality, and packaging. These advancements are expected to ensure the sustainability of honey farming, providing a stable livelihood for the community, especially honey farmers in Jujun Village